Circadian Gene Clock Regulates Psoriasis-Like Skin Inflammation in Mice - Ando, Noriko; Nakamura, Yuki; Aoki, Rui; Ishimaru, Kayoko; Ogawa, Hideoki; Okumura, Ko; Shibata, Shigenobu; Shimada, Shinji; Nakao, Atsuhito (Journal of investigative dermatology, 2015)
There are several reports suggesting that the pathophysiology of psoriasis may be associated with aberrant circadian rhythms. However, the mechanistic link between psoriasis and the circadian time-keeping system, “the circadian clock,” remains unclear. This study determined whether the core circadian gene, Clock, had a regulatory role in the development of psoriasis. For this purpose, we compared the development of psoriasis-like skin inflammation induced by the Toll-like receptor 7 ligand imiquimod (IMQ) between wild-type mice and mice with a loss-of-function mutation of Clock. We also compared the development of IMQ-induced dermatitis between wild-type mice and mice with a loss-of-function mutation of Period2 (Per2), another key circadian gene that inhibits CLOCK activity. We found that Clock mutation ameliorated IMQ-induced dermatitis, whereas the Per2 mutation exaggerated IMQ-induced dermatitis, when compared with wild-type mice associated with decreased or increased IL-23 receptor (IL-23R) expression in γ/δ+ T cells, respectively. In addition, CLOCK directly bound to the promoter of IL-23R in γ/δ+ T cells, and IL-23R expression in the mouse skin was under circadian control. These findings suggest that Clock is a novel regulator of psoriasis-like skin inflammation in mice via direct modulation of IL-23R expression in γ/δ+ T cells, establishing a mechanistic link between psoriasis and the circadian clock.